Mangifera indica L. extract (Vimang) improves the aversive memory in spinocerebellar ataxia type 2 transgenic mice - Natasha Maurmann (Journal of Pharmacy & Pharmacognosy Research, 2014)
Context: The spinocerebellar ataxia type 2 (SCA-2) is a progressive neurodegenerative disorder without specific therapy identified, and it is related to the loss of function in the cerebellum, mitochondrial dysfunction, oxidative stress and neurotoxic processes. Scientific evidence indicates that Mangifera indica L. aqueous extract (MiE) and its major constituent (mangiferin) display antioxidant, anti-inflammatory and neuroprotective actions. Aims: To investigate the MiE and mangiferin effects on behavioral outcomes of neurological function in SCA-2 transgenic mice. Methods: The SCA-2 transgenic mice were daily and orally administered during 12 months with MiE (10, 50, and 100 mg/kg), mangiferin (10 mg/kg) or vehicle. It was evaluated locomotion (open-field), aversive memory (inhibitory avoidance) and declarative memory (object recognition). To explore possible cellular mechanisms underlying the in vivo effects was also evaluated their effects on nerve grow factor (NGF) and tumor necrosis factor-α (TNF-α) levels in the human glioblastoma cell line U138-MG supernatant. Results: MiE administration did not affect the object recognition memory, but mangiferin did. The natural extract improved selectively the aversive memory in SCA-2 mice, indicating that MiE can affect behavioral parameters regarding fear-related memory. MiE also induced a significant increase in supernatant levels of NGF and TNF-α in vitro in human U138-MG glioblastoma cells. Conclusions: The results suggest that MiE enhances the aversive memory through a mechanism that might involve an increase in neurotrophin and cytokine levels. These findings constitute the basis for the use of the natural extract in the prevention/treatment of memory deficits in SCA-2.